Pemberantasan Stunting dan Penatalaksanaan Permasalahan Kesehatan Masyarakat Cerdas - Andriani, Medi; Putri, Kiki Ananda; Maharani, Juliantika; Hidayati, Atriani; Ibriyanti, Silda; Shabirah, Athayyah; Lina, Ade Okta; Cupa Munti, Putri Delina; Sandi, Putri Lara (Universitas Baiturrahim, 2025)
Stunting is a growth and development disorder in children, not only inhibiting physical growth but also other growth processes such as mental, cognitive, and intellectual development. Stunting is caused by long-term malnutrition that can occur from conception to the age of 24 months. In Indonesia, the prevalence of stunting is projected to decrease by 2.8% to 21.6% in 2022. Based on data from the Batanghari Regency Health Office, the number of young children suffering from stunting has increased compared to 2021. The results of the 2022 Indonesian Child Nutrition Survey (SDGBI) revealed that the stunting rate in Batanghari reached 26.3%, making Batanghari Regency the district/city with the highest stunting rate in Jambi Province. The purpose of this study is to increase public understanding of what stunting is, its causes, short-term and long-term risks of stunting, and how to overcome the impact of stunting. The method carried out is direct counseling to the people of Tanjung Putra village, Mersam, Batang Hari. The results obtained are 80% of the people of Tanjung Putra village know about stunting.